Village Community and Flora Biodiversity Management in Home Garden System at Central of Sumba Regency - Gerson N. Njurumana (Jurnal Penelitian Kehutanan Wallacea, 2016)
Flora biodiversity is a strategic resource due its various potential uses for human benefit. Population growth is sometimes considered to be a contributory factor in the degradation of the biological resources, conversely, the population plays an important role in its conservation. This research aimed to understand the flora biodiversity management, structure and composition of plants in home-garden system. The research was conducted in Central Sumba Regency. Methods used were interview and observation. Data were analysed descriptively and qualitatively. The result showed that the flora biodiversity management in home garden based on poly-culture approach, a holistic beneficially as a socio-cultural-religious attribute, economic-income and ecology-conservation. The structure and composition of plant in the home-garden they include the variation of the important value index. The expansion of the residential areas positively impact the flora biodiversity conservation in home-garden system.